Antidepressant use during pregnancy: Determining the impact on the gut serotonergic system in the offspring - Law, Harriet (My University, 2014)
Approximately 10% of pregnant women take antidepressants. Prenatal exposure to selective serotonin reuptake inhibitors (SSRIs), a class of antidepressants, has been shown to alter serotonergic signaling in the brain. However, the effects of SSRIs on peripheral serotonin (5HT) synthesis and/or signaling have largely been ignored. Serotonin in the gut is critical for intestinal function and dysregulation of this pathway is associated with intestinal disease. Therefore, the goal of this study was to determine the effects of perinatal exposure to the SSRI fluoxetine (Prozac®) on intestinal health in the offspring. Dams were given vehicle or fluoxetine hydrochloride (FLX 10 mg/kg/d; N=15) for 2 weeks prior to mating until weaning. We assessed markers of serotonergic signaling, inflammation, and composition of the gut microbiota in the offspring. Male offspring of fluoxetine-treated dams had significantly elevated serum levels of 5-HT and decreased expression of the 5HT2A receptor and MAO. In female offspring there was no effect of SSRI exposure to alter any components of serotonergic signaling. Although we did not find any evidence of increased inflammation following fluoxetine exposure, there were significant alterations in the composition of the gut microbiota in the exposed offspring. Male offspring of SSRIs-exposed mothers had changes in key components of the gut serotonergic system in association with elevated levels of serum 5-HT and alterations in the gut microbiota in adulthood. The impact of these changes on intestinal health and the reasons for the sex specific effects remain to be determined.
Keywords: Serotonin Selective Reuptake Inhibitor; Fluoxetine; Developmental Programming; Antidepressant; Gut; Prenatal and neonatal exposure; Effects on the offspring; SSRI